THE ROLE OF HULU SUNGAI SELATAN’S GOVERNMENT PUBLIC RELATIONS IN EDUCATING THE COMMUNITY ABOUT THE DANGERS OF COVID-19 - Sarwani Sarwani; Astinana Yuliarti (Universitas Lambung Mangkurat, 2022)
During the Covid-19 pandemic, Public Relations (PR) has a strategic function as a mediator of information from the government to the community. Public relation is an important support in achieving the goals set by an organization's management. Hulu Sungai Selatan Regency is one of the government agencies that use public relations as a means to inform the development of COVID-19. This study aims to find out how the role of the HULU SUNGAI SELATAN Regency Government Public Relations in educating the public about the dangers of Covid-19. The research method used is that the researcher uses qualitative research because he wants to emphasize the quality of the data, not the quantity of data. The results of the study indicate that the Hulu Sungai Selatan government through Public Relations has made efforts to educate the public regarding the current conditions of distribution, the number of Positive, PDP, and ODP in the Hulu Sungai Selatan Regency. Also contains policies, activities, appeals such as other important appeals, as well as activating Regional Apparatus Organizations to obtain information that will be published to the public.